O processo de criação e consolidação da primeira Companhia de Aprendizes Marinheiros do Brasil Imperial (1840) - Dias, Jorge Antonio (2017)
The thesis object is the creation and consolidation process of the first Imperial Brazilian Seaman's Apprentice Company in 1840. In this work we seek to detach the political and historical moments passed through in order to create the Seaman´s Company, discussing and examining the process based in the different ideas that permeated the actions from the different navy ministers and the specific legislations concerning the Company´s creation and registration. It was tried to develop in this work the idea that the Seaman´s Apprentice Company were, although partial and incomplete, instrumental in the process of formal instructing and educating of the seaman started in mid nineteenth century. It also serves to point out the historical contradictions between recruitment and composition squares, a relative prominence of Navy offices and Ministers different moments in the formulation of an institutional political conduct to put into practice and effective institutionalization and military uniformazing, a public institution for young people who could provide a public institution education, as rare to the “individuals of the common”; and, finally, the custody and protection of these young people.